Determinação do íon ferro em preparações farmacêuticas através da cromatografia planar e espectrofotometria - MANCINI, Maria Aparecida Donnini [UNESP]; ZUANON NETTO, José [UNESP]; VALLADÃO, Dênia Mendes de Sousa [UNESP] (Editora Unesp, 1997)
Os autores estudaram o comportamento cromatográfico de preparações farmacêuticas comerciais contendo o íon Fe (II). Utilizando celulose microcristalina/Propanol: ácido clorídrico 4 N: ácido acético concentrado: ácido nítrico concentrado: clorofórmio (40: 5: 5: 10: 10), como sistema cromatográfico e alizarina como reagente de detecção, Fe (II), Mn (II), Mg (II), Cu (II), Zn (II) e Ca (II) foram separados e identificados pela Cromatografia Planar. O Fe (II) foi determinado pela reação com a ortofenantrolina, resultando em solução adequada para quantificação colorimétrica.

The authors have studied the chromatographic behavior of pharmaceutical preparations obtained from commercial sources containing the ferrous ion. Using microcrystalline cellulose , propanol: 4 N, H Cl, acetic acid, nitric acid, chloroform mixture (40: 5: 5: 10: 10) as chromatographic system and and Alyzarin as the detection reagent Fe (II), Mn (II), Mg(II), Zn (II) and Ca (II) were separated and identificated by Planar Chromatography. Fe (II) cation was determined by reaction with 1, 10-Phenanthroline, resulting in an appropriate solution for colorimetric quantitation.
Determination of ferrous ion in pharmaceutical preparations through planar chromatography and spectrophotometry
Keywords: Cromatografia Planar; CCD; íon Fe (II); cátions; preparações farmacêuticas; Planar Chromatography; TLC; Fe (II) ion; pharmaceutical preparations